Hedgehog Signaling Pathway in Fibrosis and Targeted Therapies - Yuchen Hu; Linrui Peng; Xinyu Zhuo; Chan Yang; Yuwei Zhang (Biomolecules)
Hedgehog (Hh) signaling is a well-established developmental pathway; it is crucial for early embryogenesis, cell differentiation, and damage-driven regeneration. It is being increasingly recognized that dysregulated Hh signaling is also involved in fibrotic diseases, which are characterized by excessive extracellular matrix deposition that compromises tissue architecture and function. As in-depth insights into the mechanisms of Hh signaling are obtained, its complex involvement in fibrosis is gradually being illuminated. Notably, some Hh-targeted inhibitors are currently under exploration in preclinical and clinical trials as a means to prevent fibrosis progression. In this review, we provide a concise overview of the biological mechanisms involved in Hh signaling. We summarize the latest advances in our understanding of the roles of Hh signaling in fibrogenesis across the liver, kidneys, airways, and lungs, as well as other tissues and organs, with an emphasis on both the shared features and, more critically, the distinct functional variations observed across these tissues and organs. We thus highlight the context dependence of Hh signaling, as well as discuss the current status and the challenges of Hh-targeted therapies for fibrosis.